2008
DOI: 10.1590/s0103-21002008000100014
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Screening Program coverage in Maringá (PR), 2001 to 2006

Abstract: Objective: To evaluate the National Newborn Screening Program (NNSP) coverage in the city of Maringá, from 2001 to 2006. Methods: This is a cross-sectional research design, which verified the number of live newborns as well as the number of screened children. The study considered the children born in Maringá as well as those born in other cities but living in Maringá. Results: The NNSP did not reach the expected coverage of 100% in Maringá during the first five years of evaluation. There is a need to consider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…9 Various studies have been undertaken in Paraná addressing cystic fibrosis, either in isolation or in the context of Neonatal Screening. The majority of these address epidemiological [10][11] or nutritional 12 aspects, associated health problems, 13 diagnostic tests 14 and evaluation of the Neonatal Screening Program. 15 Only two studies were identified addressing the importance of the organization of support for those with cystic fibrosis and the intersubjectivity in the context of the family.…”
Section: Introductionmentioning
confidence: 99%
“…9 Various studies have been undertaken in Paraná addressing cystic fibrosis, either in isolation or in the context of Neonatal Screening. The majority of these address epidemiological [10][11] or nutritional 12 aspects, associated health problems, 13 diagnostic tests 14 and evaluation of the Neonatal Screening Program. 15 Only two studies were identified addressing the importance of the organization of support for those with cystic fibrosis and the intersubjectivity in the context of the family.…”
Section: Introductionmentioning
confidence: 99%
“…A qualidade das amostras para o Teste do Pezinho é um fator essencial para a eficácia e a eficiência do PTN (MARTON, LACERDA, 2003;BACKES et al, 2005). (CARVALHO et al, 2008). Considerando a América Latina, a cobertura da triagem neonatal também é heterogênea.…”
Section: Resultsunclassified